Predisposing Factors in Dental and Oral Health Care During COVID-19 - Gayatri, Rara Warih; Deniati, Ema Novita; Ekawati, Rany (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
Background: Until this study was designed, there have been no studies related to internal risk factors from the patient's side in carrying out oral health care during the COVID-19 period, especially in Malang City. The purpose of this study was to determine the relationship between internal determinants of visitors to the Malang City Health Center in carrying out dental health care during the covid 19 period.Methods: The research design in this study was quantitative observational with a cross sectional approach. In this study cluster, random sampling was conducted in 4 sub-districts in Malang. The number of samples is 343 respondents. The instrument used was a questionnaire with the variables measured were attitudes, motivations, knowledge, perceptions and actions to take care of. The analysis used was univariate using percentages, bivariate using chi-square test and multivariate using logistic regression.Result: The results of the analysis obtained that the influence on the act of performing treatment can be explained by 23.5 percent by perceptions, motivations, knowledge, and attitudes, while the rest of the other influences are explained by other factors.Conclusion: The motivation and attitude variables of the respondents showed a significant influence. Meanwhile, the respondent's perception and knowledge variable did not show any significant effect.